Analisis Kemampuan Pemecahan Masalah Matematis ditinjau dari Motivasi Belajar Matematika Siswa - Hasanah, Uswatun; Soeprianto, Harry; Triutami, Tabita Wahyu; Hayati, Laila (Mandalika Mathematics and Educations Journal, 2024)
This study aims to describe the ability of mathematical problem solving in terms of mathematics learning motivation of class VIII students of SMP Negeri 17 Mataram. The type of research used is qualitative description. The subjects in this study consisted of 11 students consisting of 4 students representing high learning motivation, 4 students of medium learning motivation, and 3 students representing low learning motivation. The data collection techniques were questionnaires, tests, and interviews. The instruments used were interview guidelines, 20 learning motivation items, and 2 problem solving ability test questions. The results showed that students with high solving ability were able to fulfill the four stages of Polya. Meanwhile, students with moderate problem-solving ability were able to fulfill two or three stages of Polya and students with low problem solving ability were unable to work on all stages of Polya.